ChemInform Abstract: Convenient One‐Pot Synthesis, Antimycobacterial and Anticancer Activities of Novel Benzoxepinoisoxazolones and Pyrazolones. Issue 37 (16th September 2014) - Saidachary, G.; Veera Prasad, K.; Divya, D.; Singh, Ashita; Ramesh, U.; Sridhar, B.; China Raju, B.
Abstract New benzoxepinoisoxazolones (II) and ‐pyrazolones (IV) are synthesized by cyclocondensation of 3‐oxo‐oxepine‐4‐carboxylates (I) with hydroxylamine or arylhydrazines, respectively.